The Effect of the Program ’ Right Intelligent System Knowledge ’ on the Development of the Critical Thinking for Students Faculty of Agriculture in University of Teashreen A quasi-experimental study - Baddour, Lina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study main to know the effect of the program ’ Right Intelligent System Knowledge ’on the development of the critical thinking for Students Faculty of Agriculture in University of Teashreen. The sample of the research was chosen intentionally , it composed of (72) students. The study had the quasi-experimental methodology in terms of dividing the research sample into two groups: the experimental group which consisted of (36) students, and the control group which consisted of (36) students. The researcher used "Right Intelligent System of Knowledge " Program: It is translated by Dr. Nadia Al-sourour in (2005), which taught the students how to think. The program consisted of four parts: Living Skills, The System, The Power of Thinking, and Success. It is suitable for students from the fifth grade till university level. And researcher used California’s Test for critical thinking: is translated by each of Abdullal Ague and Adel Albanna, and it was adopted by the current study Photo-verbal of this test, for measuring the capacity: the total score, analysis, evaluation, inference. The study showed that: there was a statistically significant difference between experimental and control groups according to California’s Test for critical thinking including with the dimensions of analysis, evaluation, inference, and the total degree as a result of the post, so this difference is due to the right intelligent system of knowledge program, and this shows the effectiveness of this program and its ability to develop critical thinking skills. Too, there was no statistically significant difference between male and female students from the experimental group on the California’s Test of critical thinking including with the dimensions of analysis, evaluation, inference, and the total degree.